INFLUENCE OF ZINC APPLICATION THROUGH SEED TREATMENT AND FOLIAR SPRAY ON GROWTH, PRODUCTIVITY AND GRAIN QUALITY OF HYBRID MAIZE - A. U. Mohsin; A.U. H. Ahmad; M. Farooq; S. Ullah (Journal of Animal and Plant Sciences, 2014)
Maize (Zea mays L.) is high nutrient demanding crop but sensitive to zinc (Zn) deficiency in soil. Application of Zn fertilizers could be a viable option to fulfill the crop demand for Zn and also to increase its contents in grains. Two years field experiments were conducted to evaluate the effect of different Zn application methods on the productivity of maize hybrids on sandy loam soil. Zinc as seed priming (1.0, 2.0% Zn solution) or foliar application (1.0, 2.0% Zn foliar spray) alone and in combinations were evaluated in randomized complete block design with factorial arrangement having three replications. Results showed that maize hybrid Pioneer 30-Y-87, with combined application of Zn as seed priming (2.0%) and foliar spray (2.0%), significantly improved plant height, cob length, cob diameter, 1000-grain weight, biological yield, grain yield and harvest index. Similarly, maize hybrid DK-919, with combined application of Zn as seed priming (2.0%) and foliar spray (2.0%) produced significantly more grain zinc content (mg kg-1). However, Zn application significantly decreased grain protein contents. These results suggested that combined application of Zn as seed priming (2.0%) and foliar spray (2.0%) can improve the performance of maize hybrids.
Keywords: Hybrid maize; zinc; seed priming; foliar spray; grain yield; zinc content; grain protein